Immigration in Singapore - Vasu, Norman; Yeap, Su Yin; Chan, Wen Ling (Asian Cities, 2014)
This study traces the sociopolitical effects of immigration on Singapore and its population, a topic that has been the subject of intense debate in the nation as its population grows increasingly diverse. Beyond the logic of economic imperatives, the book aims to explore the larger consequences of taking in large numbers of immigrants, and its analysis should appeal to scholars of migration, social change, and public policy.